Quantitative Analysis of Omega-3 Content in Fish Waste and Its Application as Aquafeed - Kiki Haetami; Abun, Abun; Putri, Aorenza Delviana; Farsya Fadillah Willyanissa; Aldiansyah, Aldiansyah; Mario Kristianto Triputra Sihombing (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Indonesia has significant potential in fisheries waste production, yet its utilization remains suboptimal due to its low economic value. However, this waste contains essential nutrients such as protein, essential fats, minerals, and vitamins that are beneficial for shrimp growth and health. Meanwhile, the high cost of commercial shrimp feed has driven the demand for more affordable alternatives, one of which is the utilization of fish waste. This study aims to analyze the omega-3 content in fish waste and evaluate its potential as an alternative feed ingredient to enhance the economic value of fisheries waste while providing nutritious feed at a reduced cost. A descriptive qualitative approach was employed through a literature review, with data collected from theses, scientific articles, and relevant journals. Data analysis was systematically conducted using the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing. The results indicate that various fish waste components (bones, skin, fins, head, and scales) contain essential nutrients including protein (≥50%), fat (≥10%), and ash (≤5%), meeting feed ingredient standards. However, it is important to note that excessive levels of unsaturated fatty acids may compromise feed quality, necessitating proper management. In conclusion, this study highlights the significant potential of fish waste as an omega-3-rich alternative feed source that can increase the economic value of fisheries waste and reduce production costs, provided that nutrient composition is carefully regulated.